Determination of lead(II), cadmium(II) and copper(II) in waste-water and soil extracts on mercury film screen-printed carbon electrodes sensor - Mohd Fairulnizal Md Noh,; Ibtisam E. Tothill, (Universiti Kebangsaan Malaysia, 2011)
A sensor incorporating a three electrodes configuration have been fabricated using low cost screen-printing technology. These electrodes couples with Square Wave Stripping Voltammetry (SWSV) has provided a convenient screening tool for on-site detection of trace levels of Pb(II), Cd(II) and Cu(II). Modification of the graphite carbon surface based on in situ deposition of mercury film has been carried out. By appropriate choice of supporting medium and optimized parameters setting such as amount of mercury used the deposition potential, deposition time, frequency and scan rate, well resolved and reproducible response for Pb(II), Cd(II) and Cu(II) were obtained. The performance characteristics of the developed mercury film screen printed carbon electrode (MFSPCE) for 120 s deposition time showed that the linear range for Cd(II), Pb(II) and Cu(II) were 10 to 200 μg L-1. The detection limit recorded for Cd(II), Pb(II) and Cu(II) were 2, 1 and 5 μg L-1 with relative standard deviation (RSD) of 6.5%, 6.9% and 7.5%, respectively. Successful applications of the sensing device to waste-water and extracted soil samples were demonstrated.